Retirement Planning Through Financial Literacy/Knowledge: A Bibliometric Analysis Perspective - Avnner Chardles Wellfren; Nelson Lajuni; Nor Shakinah Hassan; Matthew Kevin Bosi (Human Resource Management Academic Research Society (HRMARS), 2022)
Personal retirement planning is not a mandatory exercise; it is a voluntary preparation for the future. Regrettably, many are unprepared for this. Most people believe retirement planning is necessary just when they are approaching retirement or are too young to consider their retirement years. As such, retirement isn't only about relaxing in the "golden years." Instead, people must plan and invest for retirement to be financially secure during those years. This study will use bibliometric analysis to overview the published scientific literature on retirement planning. The Scopus database compiled all available retirement planning literature. The keyword search yielded 108 documents that were filtered out. In peer reviewed journals or conference proceedings, all publications were authored in English. Most of these papers were in the subjects of Economics, Econometrics and Finance, Business, Management, Accounting, and Social Sciences. The bibliometric study summaries the literature on retirement planning and identifies future research opportunities.